Impact of C-reactive protein-albumin-lymphocyte index as a prognostic marker for the patients with undergoing gastric cancer surgery - Makoto Toda; Hiroaki Musha; Takefumi Suzuki; Takashi Nomura; Fuyuhiko Motoi (Frontiers in Nutrition)
IntroductionThe significance of the C-reactive protein-albumin-lymphocyte index [CALLY index (CI)] as a prognostic factor in gastric cancer remains unexplored. Therefore, this study assessed the utility of the CI as a predictor of short-term postoperative outcomes and long-term prognosis after gastric cancer surgery.MethodsThis study consisted of two cohorts. Cohort 1 included 120 patients who underwent distal gastrectomy for clinical stages I–III primary gastric cancer between November 2022 and March 2024. Patients were categorized into high- and low-CI groups, and complications were classified accordingly. Propensity score matching was performed based on clinical stage, surgical approach, and lymph node dissection extent, yielding 40 matched cases. The relationship between preoperative CI and short-term postoperative outcomes was analyzed. Cohort 2 included 358 patients with pathological stages I–III gastric cancer who underwent distal gastrectomy between January 2014 and December 2017. Preoperative CI was assessed, and its association with long-term outcomes was evaluated. Prognostic factors were also analyzed.ResultsIn Cohort 1, the preoperative CI was associated with short-term postoperative outcomes. Compared with the high-CI group, the low-CI group developed significantly more complications, including postoperative pneumonia. In Cohort 2, the 5-year overall survival (OS) and recurrence-free survival (RFS) differed significantly between the high and low CI groups. CI was an independent prognostic factor for OS and RFS.ConclusionThe CI reflects patients' overall systemic conditions and may be a valuable predictor of short-term outcomes and long-term prognosis following gastric cancer surgery.